Para-Nonylphenol Induces Apoptosis of U937 Human Monocyte Leukemia Cells in vitro - Santa, Kazuki; Ohsawa, Tomonori; Sakimoto, Takehiko (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2016)
Background: Human autoimmune diseases are caused by a variety of factors, such as environmental chemicals, including para-nonylphenol. Macrophages play many critical roles in the regulation of immunity and the progression of autoimmune diseases. However, little information is available regarding the effects of para-nonylphenol on cellular signaling pathways and the death of these cells in vitro. Here, we show that very high concentrations of para-nonylphenol (50-100 μM) induce apoptosis in U937 human monocyte leukemia cells in a dose-dependent manner. Methods: Cell viability was judged using the trypan blue exclusion method. FACS analysis for DNA fragmentation was conducted, cellular signaling pathways were evaluated using western blot analysis, and caspase activity was measured by using substrates. U937 cells were differentiated by PMA. Results: Treatment with > 50 μM para-nonylphenol induced apoptosis in U937 monocyte cells and MCF- 7 and MDA-MB231 human breast cancer cells. We found cytochrome c release from the mitochondria to the cytoplasm, DNA fragmentation, and decreased expression of anti-apoptotic protein Bcl-XL. Caspase 3 and 9 were induced, but caspase 1 and 3-inhibitor treatment suppressed apoptosis. Para-nonylphenol decreased the levels of activated AKT and increased the levels of activated JNK/SAPK at 15 min after treatment. Furthermore, with PMA treatment, U937 cells were differentiated into a macrophage-like phenotype and showed attenuated cell death against para-nonylphenol. Conclusion: As this assay system is simple and rapid, it may represent a useful artificial tool to clarify the signaling pathways of apoptotic cell death in human monocytes in vitro.
Keywords: Bcl-XL